Undernutrition and Quality of Life in Non Small Cell Lung Cancer Patients - Xara, S (2011)
Cancer is related to a deterioration of nutritional status and quality of life (QoL), but the extent of these conditions in patients with Non Small Cell Lung Cancer (NSCLC) has not been studied. The aim of the present study was to assess the association between QoL and undernutrition in NSCLC patients. Nutritional status was evaluated with Patient Generated - Subjective Global Assessment and QoL using the European Organization for Research and Treatment of Cancer Quality of Life - C30 and also with the specific module for lung cancer patients. A consecutive sample of fifty six patients diagnosed with NSCLC was evaluated. A high proportion of patients is undernourished (35.7%), 1.8% in early stages vs 33.9% in advanced stages of disease. Undernutrition is related to measured dimensions of QoL: lack of appetite (rho = 0.70), fatigue (rho = 0.54), nausea and vomiting (rho = 0.52) and constipation (rho = 0.56). Undernourished patients have worse global health status, physical, emotional, social and role functioning. Patients with NSCLC have high frequency of undernutrition in advanced stages of disease. Undernourished patients present more symptoms, a worse global health status/QoL, physical, role, emotional and social functioning than patients without undernutrition. Undernutrition is associated with worse QoL, specifically in the parameters: appetite loss, nausea and vomiting, constipation and fatigue. (C) 2010 Published by Elsevier Espana, S.L. on behalf of Sociedade Portuguesa de Pneumologia.